Peningkatan Kecerdasan Visual-Spasial Anak Usia Dini Melalui Permainan Lego (Penelitian Tindakan Kelas Pada Kelompok A) - Suchaimiyah Suchaimiyah; Laini Lathifah (PG-PAUD Trunojoyo, 2016)
This research aims to improve children”s visual-spatial intelligence through lego models and determine the extent of the resulting increase in visual-spatial intelligence of children through games lego in KBM NU 20 Islamiyah Ujungpangkah Gresik. This research conducted in KBM NU 20 Islamiyah Gresik this research conducted in KBM NU 20 Islamiyah Ujungpangkah Gresik at the age 3-4 years the number of students as much as 7 children. The method used in this research is a classroom action research that refers to a class action research model of kurt lewin which includes four stages planing, acting, observating. This study consisted of two cycles, each cycle consisting of two meetings. Analysis of the data used quantitative and qualitative approaches. The results showed an increase in visual-spatial intellingence through lego models, can be demonstrated average visual-spatial intellingence scores first cycle of children by 90%. Then an increase in cycle II by 95%. So that the total increase in visual-spatial intelligence of children start pre-action, the firs cycle II is 95%.